ДИАХРОН ӘДИСТЕ ИЗЕРТЛЕНГЕН ИНГЛИС ТИЛИНДЕГИ ӨЗЛЕСКЕН СӨЗЛЕРДИҢ АНАЛИЗИ - Бердиханова, А.Ж. (FAN va JAMIYAT, 2023)
This suggested article is written in empiric style, so the main goal is to analyse borrowing words properly. That is to say, most borrowings are not disappearing on the contrary loan words are developing.